2021
DOI: 10.3390/life11121322
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Microbiome for Forensic Geolocation: A Review

Abstract: Forensic microbiomics is a promising tool for crime investigation. Geolocation, which connects an individual to a certain place or location by microbiota, has been fairly well studied in the literature, and several applications have been found. The aim of this review is to highlight the main findings in this field, including the current sample storage, DNA extraction, sequencing and data analysis techniques that are being used, and its potential applications in human trafficking and ancient DNA studies. Second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Various studies have shown that the bacterial species present in deceased individuals (such as Helicobacter pylori) or adult hair matrices in different cities can be used to predict an individual's geolocation, due to climate, rainfall, altitude, soil and energy sources in the environment [176].…”
Section: Violence Violent Death and Forensic Microbiologymentioning
confidence: 99%
“…Various studies have shown that the bacterial species present in deceased individuals (such as Helicobacter pylori) or adult hair matrices in different cities can be used to predict an individual's geolocation, due to climate, rainfall, altitude, soil and energy sources in the environment [176].…”
Section: Violence Violent Death and Forensic Microbiologymentioning
confidence: 99%
“…Some studies have also revealed variation in the human microbial ecology of different populations around the world, highlighting the potential for detecting microbial signatures that are specific to geographical regions (Brinkac et al, 2018;Cho & Eom, 2021;Grantham et al, 2019;Haarkötter et al, 2021;Lax et al, 2015). This requires the creation of a robust and reliable international microbiome database containing an adequate sample size and associated metadata (e.g., geographic origin, ethnic group) for geolocation purposes, such as the Forensic Microbiome Database which currently contains microbiomes from 35 countries (139 cities; Singh et al, 2021).…”
Section: Forensic Microbiomicsmentioning
confidence: 99%
“…In this context, the Earth Microbiome Project was created in 2010 (https://earthmicrobiome.org/; last accessed on 30 June 2023) to sample the whole planet's microbial communities and, thus, to assess biogeographic variations of microbial communities. Each city shows unique microbial profiles contributing with high accuracy to the geographical identification of the place of death or surrounding areas [105]. Available studies exploring the use of microbial profiles for geolocation showed, among other promising data, clear differences in the most common species in people from different cities in different countries.…”
Section: Geolocationmentioning
confidence: 99%